Measurement of Human Development: an alternative approach - Shoutir Kishore Chatterjee (Journal of Human Development Vol. 6, No. 1, March 2005, 2005)
The quality of life of an individual is standardly regarded as having three dimensions: (i) prospective longevity, (ii) educational attainment and (iii) standard of living. An index of human development in a population should be based on the distribution of characters representing these in the population and should ideally take account of both the general level and the extent of inequality (i.e. equality or concentration) in the `values' of each character. The Human Development Index of the United Nations Development Programme nowadays takes account of only the general levels of the characters - such as expectation of life for, (i) literacy rate and enrolment ratio for, and (ii) Gross Domestic Product per capita for. In this paper first a joint measure of the general level and concentration of the distribution of an ordered qualitative or a quantitative character is proposed. The measure is then applied on the distribution of prospective longevity, educational level and income, and an alternative Human Development Index is set up on that basis. The method is illustrated by computing the proposed index for the rural and urban sectors of a number of Indian States and of India as a whole